Alfred Jarry et Jacques Lacan. Lalangue du Docteur Faustroll - Sallustio, Jérémie (Romanica Silesiana)
This article tackles the issue of alienation in the Gestes et opinions du Docteur Faustroll, pataphysicien, by Alfred Jarry. To do so, it analyzes a few of the metaphorical islands found in Book III, “De Paris à Paris par mer”. The analysis also posits a link with a lacanian concept: lalangue. Key words: Alfred Jarry, Jacques Lacan, alienation, Island